Effects of underground explosions on soil and structures - Ambrosini, Ricardo Daniel (2020)
Much effort has been dedicated to the study of underground explosions because they pose a major threat to people and structuresbelow or above the ground. In this regard, it is especially important to model the propagation of blast waves in soil and their effectson structures. The main phenomena caused by underground explosive detonation that must be addressed are crater or camouflet forma-tion, shock wave and elastic?plastic wave propagation in soil, and soil-structure interaction. These phenomena can be numerically sim-ulated using hydrocodes, but much care must be taken to obtain reliable results. The objective of this study is to analyze the ability of ahydrocode and simple soil models that do not require much calibration to approximately reproduce experimental and empirical resultsrelated to different buried blast events and to provide general guidelines for the simulation of this type of phenomena. In this regard,crater formation, soil ejecta, blast wave propagation in soil, and their effects on structures below and above the ground are numericallysimulated using different soil models and parameters; the results are analyzed. The properties of soil have a significant effect on struc-tures, the ejecta, and the propagation of shock waves in soil. Thus, the model of the soil to study these phenomena must be carefullyselected. However their effect on the diameter of a crater is insignificant.